PROGRAM KEMITRAAN MASYARAKAT STIMULUS UMKM MARNING DI DESA MASDA MAKMUR - Rina Ari Rohmah; Purwantoro Purwantoro; Erni Rouza (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P2M) IKIP Budi Utomo Malang, 2019)
The Stimulus Community Partnership Program ( PKMS ) was implemented at the UMKM Marning Mbok Jas. In this stimulant community partnership program there are three efforts to solve the problems faced by partners, namely the first increase in the ability of science and technology in the production system, this effort is made to increase production productivity, optimize production and improve hygienic marning quality. The second effort is to increase the variant of the production of processed corn and corn marning; it aims to increase the variant of corn marning products, namely to increase the variant of corn marning flavor. By creating a third effort which is to change the marketing strategy by creating a taste that consumers like and a consistent taste, making brochures, and labeling it to look attractive and other marketing activities and marketing in the marketplace.